Monetary policy and inequality: The Finnish case - Petri Mäki-Fränti; Aino Silvo; Adam Gulan; Juha Kilponen (Bank of Finland, 2022)
We use Finnish household-level registry and survey data to study the effects of ECB's monetary policy on the distribution of income and wealth. We find that monetary easing has a large positive effect on aggregate economic activity in Finland, but its overall net impact on income and wealth inequality is negligible. Monetary easing increases households' gross income by reducing unemployment and leading to a general rise in wages, while at the same time it boosts asset prices. These different channels have counteracting effects on income and wealth inequality, as measured by the Gini coefficient and the ratios of income and wealth of the 90th percentile to the 50th percentile. The reduction in aggregate unemployment benefits especially households in lower income quintiles, where the initial rate of unemployment is high. Households in the upper income quintiles, where the rate of employment is higher, benefit relatively more from an increase in wages. An increase in house prices benefits all homeowners. In terms of net wealth, households with large mortgages, in the lower wealth quintiles, benefit the most from an increase in house prices due to a leverage effect. An increase in stock prices, in turn, benefits mainly households in the top wealth quintile.
URN:NBN:fi:bof-202201181021
Keywords: D31; E32; E52; 330; monetary policy; income inequality; wealth inequality